Komodifikasi Budaya dalam Wacana Pariwisata: Analisis Wacana Kritis Brosur Tour Packages Solo Raya - Adiwinata, Akbar; Muhid, Abdul (Samsara Institute Publisher, 2025)
This study aims to reveal how the culture and the society of Solo are represented in the tourism brochure — Tour Packages Solo Raya published by The Department of Culture and Tourism of Surakarta City. The research employes Norman Fairclough’s model of Critical Discourse Analysis (CDA), examining the text through three level of analysis: textual description, discourse practice interpretation, and social practice explanation. The focus of the study includes: (1) identifying culture representations through lexical choices and narrative patterns, (2) exploring dominant discourse and their underlying ideological and economic interest, (3) examining the process of cultural commodification, and (4) analyzing the role of linguistics inaccuracies in shaping the image of the tourist destination. The findings indicate that the brochure text represents Solo’s culture as a “package of attractions” consumable by tourists, where everyday life is positioned alongside other tourism objects. The dominant discourse that emerges is tourism as a commodity, underpinned by an ideology of local economic development directed toward market appeal. Cultural elements undergo a reduction of meaning when framed merely as entertainment, detached from their social and spiritual contexts. Furthermore, typographical errors, awkward sentences, and non-standard promotional language illustrate the mismanagement of image construction, potentially undermining the seriousness of Solo’s tourism branding.